Which perspectives can endophenotypes and biological markers offer in the early recognition of schizophrenia? - Bender, Stephan; Weisbrod, Matthias; Resch, Franz (Journal of neural transmission, 2007)
The early recognition of schizophrenia seems crucial; various studies relate a longer duration-of-untreated-psychosis to a worse prognosis. We give an overview over common psychopathological early recognition instruments (BSABS, CAARMS, SIPS, IRAOS, ERIraos). However, many clinical symptoms of prodromal schizophrenia stages are not sufficiently specific. Thus we review recent contributions of neuroimaging and electrophysiological as well as genetic studies: which new diagnostic perspectives offer endophenotypes (such as P300, P50 sensory gating, MMN, smooth pursuit eye movements; indicating a specific genetic vulnerability) together with a better understanding of schizophrenic pathophysiology (state-dependent biological markers, e.g. aggravated motor neurological soft signs during psychosis) in prodromal schizophrenia when still ambiguous clinical symptoms are present. Several examples (e.g. from COMT polymorphisms to working memory deficits) illustrate more specific underlying neuronal mechanisms behind behavioural symptoms. This way, a characteristic pattern of disturbed cerebral maturation might be distinguished in order to complement clinical instruments of early schizophrenia detection.